The Moderating Impact of Religion and Women's Business on Household Economic Security: A Financial Planning Perspective - ceta indra lesmana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The household economy in Indonesia plays a crucial role in the dynamics of the national economy. However, data from the Central Statistics Agency (BPS) in 2022 reveals that the average per capita household expenditure is still below the poverty line, reaching IDR 4,225,000 per month. This highlights a significant challenge in efforts to improve household welfare in Indonesia. This research provides policy suggestions to overcome these problems, including increasing access to education and skills, strengthening social protection programs, and supporting the development of small and medium enterprises (SMEs). Financial literacy, access to financial services, and the role of women in the economy are also important focuses in designing a comprehensive strategy. Collaboration between government, the private sector and non-governmental organizations is needed to realize effective policy implementation. Finally, the promotion of a green economy is proposed as a progressive step to create sustainable jobs and encourage inclusive economic growth. It is hoped that this research can provide a holistic view of household economic problems in Indonesia and provide direction for developing more effective and sustainable policies.